AICCRA Ghana Accelerator Platform: Strengthening public–private partnerships for scaling climate-smart innovations - Yeboah, Stephen; Dalaa, Mustapha Alasan; Obeng, Faustina; Tepa-Yotto, Ghislain (2025)
Farm productivity among smallholder farmers is continuously affected by climate variability and ecological changes, leading to socio-cultural, economic, and environmental challenges and vulnerabilities (Antwi-Agyei et al. 2021). Productivity in farmers’ fields remains low, and several reasons account for this. Notable among these reasons is the continuous reliance on unimproved seeds and or low access to improved technologies (Quarshie et al.,2023; Yeboah et al., 2019). To provide secure and safe food in Ghana, prevent the development of resistance to pests in crops and animals, and their attendant public health implications, and reduce the vulnerability of smallholders requires urgent efforts to curb the effects of climate change on food production. While this is of strategic importance, climate-smart agriculture (CSA) and associated climate-informed services (CIS), as well as one-health innovations, are needed to enhance the resilience of food production and its safety, but the access by end users is limited.